Tracing the origin of raw milk from farm by using Automated Ribosomal Intergenic Spacer Analysis (ARISA) fingerprinting of microbiota. (April 2015) - Feligini, Maria; Panelli, Simona; Sacchi, Roberto; Ghitti, Michele; Capelli, Enrica
Abstract: The aim of the study was to distinguish the raw milk from different farms in relation to their geographical sites within a narrowed territorial district. The goal was achieved by applying a molecular-based system for traceability that uses microbial DNA barcodes present in milk. Microbiota of milk were fingerprinted by PCR of the 16S–23S intergenic transcribed spacer using the Automated Ribosomal Intergenic Spacer Analysis (ARISA). A total of 64 markers within the range 279–756 bp were detected on the thirty-eight bulk milk samples, none of which was common to all the patterns. Overall samples did not show relevant differences across the two years of sampling. In fact, every farm maintained a specific core profile over time, thus demonstrating that the interaction between site and year of sampling is not significant and that the variability between years does not affect the distinction between grouping of farms. The system was able to trace the geographical origin of raw milk with a resolution of less than 5 km. According to the European regulations for the protection of the geographical names of foodstuffs which have a tangible link to the territory, the ARISA system described here may represent a suitable analytical tool for tracing the origin of milk integrating and reinforcing traceability processes of the dairy chain. Highlights: The challenge is to use microbial fingerprinting of milk to trace its origin. An original ARISA system based on barcodes was developed. The system was validated "in field" on bulk raw milk from individual farms. The results establish that each milk exhibited a specific core profile over time. The ARISA system is able to map the farms with a resolution <5 km.